THE INFLUENCE OF MESSAGES IN SOCIAL MEDIA ON TAXPAYER COMPLIANCE - Latifah Hanum; Rama Semida Nehemia Makatita; Chatarina Oktaviani Chatarina Oktaviani; Diana Dwi Vally Febrianti; Kadek Dwi Kadek Dwi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
This study integrates the Theory of Planned Behavior (TPB) and the Elaboration Likelihood Model (ELM) to assess and explain taxpayers' compliance with the Twitter account @DitjenPajakRI. This is a quantitative study with an explanatory approach. A purposive sample strategy was used with a questionnaire to collect data for this research. A total of 200 people filled out the research questionnaire. According to the study’s findings, Source Credibility influences Attitudes, and the two TPB components, Attitudes and Perceived Behavioral Control, influence Taxpayer Compliance. As for the relationship between Argument Quality and Source Credibility on Attitudes, there is no moderating effect of Involvement; instead, the relationship between Source Credibility and Taxpayer Compliance through Attitudes is a full mediation relationship. The findings of this study can assist the tax authority in developing strategies and policies for efficiently and effectively communicating tax information to taxpayers as they make decisions about how to fulfill their tax rights and obligations through messages from central route, peripheral route, normative, and non-volitional processes.